La baisse de la polyvalence avec l’âge : question de vieillissement, d’expérience, de génération ? - Corinne Gaudart (Perspectives Interdisciplinaires sur le Travail et la Santé)
Reduced versatility with age is a trend that has been observed in the last few years in French statistical investigations. The explanations most frequently given are a reduction in motivation with age and difficulties in adapting to changes. However, ergonomic studies, in this case in the industrial sector, show that there are many explanations. They involve the possibility of transferring one’s experience, which, with age, integrates self-preservation strategies ; this experience is developed individually and collectively, depending on the situation. The explanations also have to do with the organizational conditions for learning and training. Furthermore, the critical threshold beyond which versatility diminishes varies with the ages of the populations, and is inherent in the generations and the history of the organizations.